Preliminary evaluation of the Healthy Savings Program: a novel health insurance-based wellness programme to encourage healthy food purchases. Issue 15 (6th July 2018) - Tang, Xuyang; Honors, Mary Ann; Fertig, Angela R; French, Simone A; Abraham, Jean; Harnack, Lisa
Abstract: Objective: To examine level of participation and satisfaction with the Healthy Savings Program (HSP), a programme that provides price discounts on healthier foods. Design: For Study 1, a survey was distributed to a random sample of adults who were invited to participate in a version of the HSP that provided a discount for the purchase of fresh produce and discounts on other healthier foods. In Study 2, interviews were conducted with a convenience sample of adults invited to participate in a version of the HSP that provided price discounts on specific products only (no fresh produce discount). Setting: The HSP is provided to all employer-based insurance plan members of a large health plan. Employers can choose to enhance the version of the HSP that their employees receive by paying for a weekly discount on fresh produce. Subjects: Employees in employer groups that received the enhanced HSP (Study 1) and employees in an employer group (Study 2) that received the standard HSP. Results: Among survey respondents in Study 1, 69·3 % reported using the HSP card. Most were satisfied with the fresh produce discount and ease of use of the HSP card. Satisfaction was lower for selection of participating stores, amounts of discounts and selection of discounted products. In Study 2, barriers to the use of the HSP card cited included the limited number of participating stores and the limited selection of discounted products. Conclusions: Satisfaction with some elements of the HSP was high while other elements may need improvement to increase programme use.